Effect of maleic anhydride-grafted-polyethylene (MAPE) and silane on properties of recycled polyethylene/chitosan biocomposites - Salmah, Husseinsyah, Prof. Madya Ir. Dr. (Taylor and Francis Group, 2014)
Link to publisher's homepage at www.taylorandfrancisgroup.com/‎